Pengkajian Status Keberlanjutan Budidaya Ternak Kerbau (B. Bubalis bubalis) Berbasis Masyarakat Di Kecamatan Sekernan Kabupaten Muaro Jambi Provinsi Jambi - Hutwan Syarifuddin; Dodi Devitriano; A Rahman Sy (Universitas Batanghari Jambi, 2022)
This research has been conducted in The Sekernan District of Muaro Jambi Regency against the people who raise buffalo traditionally. The purpose of the study is to find out the status of the sustainability index and the attributes that affect in the cultivation of buffalo cattle traditionally by the community in Sekernan Subdistrict. The research uses Rapker's method through surveys and interviews on buffalo farmers relating to ecological dimensions, economic dimensions and socio-cultural dimensions. The results showed that the ecological dimension was 42.81% with sensitive attributes of buffalo animal feed types (3.89) and land availability for animal feed (3.11). Economic dimension 46.67% with sensitive attributes of the number of livestock labor (5.16) and the feasibility of agroindustry business (2.41). The socio-cultural dimension is 42.56% with sensitive attributes of extension and training frequency (3.58) and employment rate of livestock labor (3.31). This indicates that the traditional cultivation of buffalo in Sekernan Subdistrict is less sustainable.